Anti-proliferative and apoptosis-inducing activities of juglone in LS-174T cells - Qiang Li; Xue-Ling Zhao; Juan Sun; Shou-Gang Jiang; Gong Xianfeng (Bangladesh Pharmacological Society, 2013)
Anti-proliferative and apoptosis-inducing effects of juglone in LS-174T cells were investigated. In this study, we showed that juglone inhibited the proliferation of LS-174T cells in a time and dose-dependent manner, treatment of juglone resulted in the activation of caspase-9 and caspase-3, decrease of Bcl-2. N-acetylcysteine significantly attenuate LS-174T cell death induced by juglone (p<0.001). In addition, NAC could reverse caspase-3 and caspase-9 activation, increase expression of Bcl-2 protein. Taken together, these findings indicated that juglone-mediated oxidative injury may act as upstream change, trigger ROS release, Bcl-2 modulation, caspase activation, and consequently leading cell apoptosis in LS-174T cells. In conclusion, these findings suggest that juglone may be an effective way for treating human cancers.